Prenatal and Early Postnatal Behavioural Programming in Laying Hens, With Possible Implications for the Development of Injurious Pecking - De Haas, Elske N.; Newberry, Ruth C.; Edgar, Joanne; Riber, Anja B.; Estevez, Inma; Ferrante, Valentina; Hernandez, Carlos E.; Kjaer, Joergen B.; Ozkan, Sezen; Dimitrov, Ivan; Rodenburg, T. Bas; Janczak, Andrew M. (Frontiers in Veterinary Science, 2021)
Injurious pecking (IP) represents a serious concern for the welfare of laying hens (Gallus gallus domesticus). The risk of IP among hens with intact beaks in cage-free housing prompts a need for solutions based on an understanding of underlying mechanisms. In this review, we explored how behavioural programming via prenatal and early postnatal environmental conditions could influence the development of IP in laying hens. The possible roles of early life adversity, and mismatch between early life programming and subsequent environmental conditions, are considered. We reviewed the role of maternal stress, egg conditions, incubation settings (temperature, light, sound, odour) and chick brooding conditions on behavioural programming which could be linked to IP. Brain and behavioural development can be programmed by pre- and postnatal environmental conditions, which if suboptimal could lead to a tendency to develop IP later in life, as we indicated by a Jenga tower which could flip over if not build solidly. If so, steps taken to optimize the environmental conditions of previous generations, incubation conditions, reduce stress around hatching and guide the early learning of chicks will aid in prevention of IP in commercial laying hen flocks.